Identification of a Naturally Occurring Recombinant Isolate of Sugarcane Mosaic Virus Causing Maize Dwarf Mosaic Disease - Zhong, Yongwang; Guo, Anyuan; Li, Chunbo
The complete nucleotide sequence of a potyvirus causing severe maize dwarf mosaic disease in Shaanxi province, northwestern China was determined (GenBank accession No. AY569692). The full genome is 9596 nucleotides in length excluding the 30-terminal poly (A)sequence. It contains a large open reading frame (ORF)flanked by a 149 nt 50-untranslated region (UTR)and a 255 nt 30-UTR. The putative polyprotein encoded by this large ORF comprises of 3063 amino acid residues. Sequence comparisons and phylogenetic analyses showed that this potyvirus is an isolate of Sugarcane mosaic virus (SCMV). The entire sequencesshared identities of 89.6-97.6percent and 79.3-93.3percent with 9 sequenced SCMV isolates at the nucleotide and deduced amino acid levels, respectively. But it showed much lower identities with Maize dwarf mosaic virus (MDMV), Sorghum mosaic virus (SrMV)and Johnsongrass mosaic virus (JGMV)isolates. The putative coat protein sequence is identical to that of a Chinese maize isolate SCMV-HZ. However, partition comparisons and phylogenetic profile analyses of the viral nucleotide sequences indicated that it is a recombinant isolate of SCMV. The recombination sites are located within the 6K1 and CI coding regions.
Keywords: MAIZE DWARF MOSAIC DISEASE; PHYLOGENETIC ANALYSIS; POTYVIRUS; SUGARCANE MOSAIC VIRUS; VIRUS RECOMBINATION